Public health and the risk factor : a history of an uneven medical revolution - Rothstein, William G. (Rochester studies in medical history., 2003)
Describes the evolution of a concept that has become central to public health and medical thought: the risk factor. The risk factor concept has been controversial because of its statistical methodology, its multifactorial concept of disease etiology, and its effect on the economic interests of commercial, professional, and health organisations. The author uses nontechnical language to guide readers through a wide array of 18th-, 19th-, and 20th-century technical developments that are the basis of our current understanding of the risk factor concept.